Workshop Findings - Moreno Beguerisse, Mariale; Charnley, Fiona; BESSIERE, Dorothée; Tiwari, Ashutosh (Cranfield University, 2017)
Thematic Analysis regarding 3 workshops conducted by the RECODE Network on the Vision of RdM for the UK's consumer goods industry.;'Thematic Analysis regarding 3 workshops conducted by the RECODE Network on the Vision of RdM for the UK's consumer goods industry'
Keywords: re-distributed manufacturing'; 'consumer goods sector'; 'localisation'; 'customisation'; 'big data'; 'Manufacturing Management'; 'Manufacturing Processes and Technologies (excl. Textiles)'